DYNAMICS OF LIQUID PENETRATION INTO TEXTILE MATERIALS TAKING INTO ACCOUNT NONLINEAR EFFECTS - RIABCHYKOV, MYKOLA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Water penetration in many cases determines the functionality of products, in particular in special garments, as well as in medical textiles. Water penetration affects the comfort and durability of products. Existing models of water penetration have a number of shortcomings, the main of which is the impossibility of taking into account the effects of the accumulated liquid on further sorption processes.The article analyzes the shortcomings of existing linear models of fluid passage. The presence of two processes is noted. The first of them determines the intensity of fluid movement. The second process affects this intensity with a certain accumulation of liquid in the material. Taking into account two processes leads to the need to solve a nonlinear differential equation in partial derivatives. A simplified method that takes into account the small thickness of the material is proposed. At the same time, the task is reduced to finding the concentration inside the material. The equation reduces to a differential equation in which the variables can be separated. As a result, an analytical solution was obtained, which takes into account nonlinear processes during liquid accumulation and includes two parameters that determine the sorption properties of the material.Numerical verification showed a significant difference between the obtained results and linear models. Water penetration rates for real fluid accumulation rates differ by 20-30%. Adequacy of the obtained model is confirmed by approximation to known experimental data. The obtained results prove the need to take into account nonlinear effects when determining indicators of fluid accumulation. The developed model allows you to solve practical problems taking into account the indicators of the passage and accumulation of liquid in textile materials and products.
Keywords: коефіцієнт накопичення; текстильні матеріали; проникнення рідини; нелінійні рівняння